Baseline dasabuvir resistance in Hepatitis C virus from the genotypes 1, 2 and 3 and modeling of the NS5B-dasabuvir complex by the in silico approach - Akaberi, Dario; Bergfors, Assar; Kjellin, Midori; Kameli, Nader; Lidemalm, Louise; Kolli, Bhavya; Shafer, Robert W.; Palanisamy, Navaneethan; Lennerstrand, Johan (Infection ecology & epidemiology, 2018)
Background: Current combination treatments with direct-acting antiviral agents (DAAs) can cure more than 95% of hepatitis C virus (HCV) infections. However, resistance-associated substitutions (RASs) may emerge and can also be present in treatment-naïve patients. Methods, results and discussion: In this study, a semi-pan-genotypic population sequencing method was developed and used to assess all NS5B amino acid variants between residue positions 310 and 564. Our method successfully sequenced more than 90% of genotype (GT) 1a, 1b, 2b and 3a samples. By using the population sequencing method with a cut-off of 20%, we found the dasabuvir RASs A553V and C445F to be a baseline polymorphism of GT 2b (8 out of 8) and GT 3a (18 out of 18) sequences, respectively. In GT 1a and 1b treatment-naïve subjects (n=25), no high-fold resistance polymorphism/RASs were identified. We further predicted dasabuvir’s binding pose with the NS5B polymerase using the in silico methods to elucidate the reasons associated with the resistance of clinically relevant RASs. Dasabuvir was docked at the palm-I site and was found to form hydrogen bonds with the residues S288, I447, Y448, N291 and D318. The RAS positions 316, 414, 448, 553 and 556 were found to constitute the dasabuvir binding pocket.